2013
DOI: 10.1177/0143624413478436
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of the CIBSE design summer year approach for delivering representative near-extreme summer weather conditions

Abstract: Representative, site-specific weather data is a key requirement for building performance simulation. In the UK, such data is available in two formats, Test Reference Years for analysing building services loads under 'typical' year conditions and Design Summer Years for estimating summer discomfort of naturally ventilated and free-running buildings. Currently, Design Summer Years are determined as a complete year based on the rank of the average dry bulb temperature from April to September. The simplicity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(61 citation statements)
references
References 13 publications
2
59
0
Order By: Relevance
“…Further work 9 showed that the methodology could produce weather files which generated the average energy use from the thousands of weather years from the UKCP09 weather generator. Similarly Jentsch et al 10 found that the TRY mean monthly temperature sits within the centre of the long-term data as would be expected.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Further work 9 showed that the methodology could produce weather files which generated the average energy use from the thousands of weather years from the UKCP09 weather generator. Similarly Jentsch et al 10 found that the TRY mean monthly temperature sits within the centre of the long-term data as would be expected.…”
Section: Introductionsupporting
confidence: 62%
“…The method for selecting candidate months for the TRY has long been established and as described above the method has been found to be robust [8][9][10] . Although the method is detailed formally elsewhere 1,6 , for completeness the method will be briefly described.…”
Section: Methods For Creating New Test Reference Yearsmentioning
confidence: 99%
“…The DSY is the year that falls in the middle of the upper-quartile of the base years' dataset, ranked according to summertime (April to September) average dry bulb temperature; this is generally the third warmest summer for a base dataset of 20 years. The DSY does not take into account extreme temperatures in individual months or incident solar radiation, both of which are of great significance for assessing the overheating performance of buildings [17]. This means that periods of high temperature (such as heat waves) in relatively cool summers are not considered.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Furthermore, as it is known that different weather parameters have a differing influence on the relative risk of overheating for different building types [23], three design reference years were selected in [26] based on the daily mean temperature, relative humidity and solar radiation respectively. In addition, different sampling methods [26,27] and statistical adjustment methods [28] have been used to develop new DSYs but none of them have been found to overcome all the shortcomings in the simple DSY selection discussed in [29].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…For instance, among the 21 years, years with significant amounts of missing data were discarded so that the number of complete years available for each site varied from 6 (Southampton and Swindon) to 21 (Edinburgh and Glasgow). Thus DSYs exist for sites with a small number of complete years which hence might not be particularly warm compared to the long-term mean [12]. CIBSE also provides Test Reference Years (TRY), which are used for predicting the energy consumption of buildings.…”
Section: Introductionmentioning
confidence: 99%